Pengaruh Kemudahan Penggunaan, Risiko dan Kepercayaan dalam Penggunaan Layanan QRIS terhadap Tingkat Kepatuhan Muzakki di LAZISMU Sulawesi Selatan - Bakri, Sri Wahyuni; Anwar, Nurfiah; Muslihati, Muslihati (Asian Journal of Islamic Studies and Da'wah, 2024)
This research aims to determine the influence of ease of use, risk and trust in using Qris services on the level of muzakki compliance in Lazismu, South Sulawesi. Where the sample in this research is muzakki who use Qris services on the level of compliance of Muzakki in Lazismu, South Sulawesi. The method used in this research is a quantitative method with a survey method. Based on the research results, it was found that the first hypothesis was accepted, namely that ease of use had a positive and significant impact on the level of muzakki compliance in Lazismu South Sulawesi regarding the use of Qris services. Likewise, the second and third hypotheses are also accepted, where risk and trust play a positive and significant role in the level of compliance of muzakki in Lazismu, South Sulawesi in using Qris services. And with that, the fourth hypothesis is also accepted, showing that together or simultaneously ease of use, risk, and trust have a positive and significant impact on the level of Muzakki compliance in Lazismu, South Sulawesi.